Parents behavior regarding communication with their adolescent concerning HIV/aids - Stella Maia Barbosa; Patrícia Neyva Pinheiro da Costa; Neiva Francenely Cunha Vieira (Rev Rene)
The aim of this study is to know about the communication between parents and their adolescent children concerning sex/sexuality and HIV/AIDS as well as prevention methods. 26 parents of adolescents registered in a public school in Fortaleza were interviewed. The results showed that most of the parents have motivation and interest in talking to their children concerning the subject, even though some showed to have had some difficulties approaching the subject with their children, despite the conversations they had with them. It was found that in families it is predominant a warning communication approach rather than clarifying preventive measures concerning HIV/AIDS or an unexpected pregnancy. Health professionals need to adopt strategies for a more informative dialogue with parents and adolescents regarding all the different situations due to unprotected sexual relations. There is a need to renew the quality and the way of giving out this information, so that the population can really put into practice safe sex measures.